INCREASING OF RED PALM OIL PREFERENCES WITH ADDITION OF VEGETABLE OIL OR FLAVOUR AND IT’S STABILITY IN REPEATED FRYING - Hasibuan, Hasrul Abdi; Ijah, Ijah (Jurnal Penelitian Kelapa Sawit, 2018)
Red palm oil (RPO) is a crude palm oil (CPO) processed product which still contains carotene (as a provitamin A) in high quantities. Unfortunately, the RPO has not been sought by the people in Indonesia because the color is reddish and has a distinctive smell. This study was conducted to increase the acceptance of RPO by adding strongly scented vegetable oils such as palm kernel oil, coconut oil, and cocoa butter of 10 - 30% or flavour of butter of 0.05 - 3%. In addition, this research was conducted to stability test of RPO, mixture of RPO:coconut oil and RPO with flavour in deep frying of potato as much as 10 times of frying. Mixing of RPO with vegetable oil or flavor can change the characteristics, improve the quality and preferences of panelists. The higher concentration of vegetable oil or flavour increasing preferences of panelist to RPO flavour. Coconut oil is the oil that has the highest level of fondness. The use of flavour that acceptable from its appearance is as much as 0.5%. Mixture of RPO:coconut oil (80:20) and RPO with 0.5% flavour have high stability during repeated frying and its preferences level of fried products is also increased compared to RPO.